2011
DOI: 10.1159/000321369
|View full text |Cite
|
Sign up to set email alerts
|

A Vitamin E-Coated Polysulfone Membrane Reduces Serum Levels of Inflammatory Markers and Resistance to Erythropoietin-Stimulating Agents in Hemodialysis Patients: Results of a Randomized Cross-Over Multicenter Trial

Abstract: Background: Oxidative stress is prevalent in dialysis patients and has been implicated in the pathogenesis of cardiovascular disease and anemia. Vitamin E is a fat-soluble antioxidant that plays a central role in reducing lipid peroxidation and inhibiting the generation of reactive oxygen species. The aim of this cross-over randomized study was to compare the effects of a vitamin E-coated polysulfone (Vit E PS) membrane and a non-vitamin E-coated polysulfone (PS) membrane on inflammatory markers and resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 48 publications
(28 reference statements)
4
53
2
Order By: Relevance
“…4 In addition, the circulating biomarkers of oxidative stress and chronic inflammatory cytokines such as malondialdehyde (MDA), C-reactive protein (CRP) or interleukin-6 (IL-6) are significantly elevated in maintenance HD patients. 5,6 There is increasing evidence that increased oxidative stress and inflammatory cytokines play a key role in the pathogenesis of malnutrition, 7 resistance to erythropoietin, 8 …”
Section: Introductionmentioning
confidence: 99%
“…4 In addition, the circulating biomarkers of oxidative stress and chronic inflammatory cytokines such as malondialdehyde (MDA), C-reactive protein (CRP) or interleukin-6 (IL-6) are significantly elevated in maintenance HD patients. 5,6 There is increasing evidence that increased oxidative stress and inflammatory cytokines play a key role in the pathogenesis of malnutrition, 7 resistance to erythropoietin, 8 …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the authors concluded that VitabranE membranes have potentially beneficial effects on ERI of HD patients. This conclusion was confirmed in another and more recent multicenter study by Panichi et al, 2011. In this report, a crossover design was employed and 62 HD patients from 13 dialysis units were randomized to receive treatments with VitabranE or polysulfone dialyzer controls.…”
Section: Improvement Of Anemiamentioning
confidence: 52%
“…In the report by Panichi et al, 2011, the authors observed that beside of ERI reduction, CRP and IL-6 levels decreased during VitabranE treatment, whereas no significant changes were found during the control polysulfone treatment. The study by Mandolfo et al (in press) on catheterized patients with a high inflammatory burden also reported a better control of CRP levels during the VitabranE treatment.…”
Section: Improvement Of Inflammatory Markersmentioning
confidence: 96%
“…Another study shows new positive effects of vitamin E-coated membranes on blood pressure level in dialysed patients (Matsamura et al, 2010). Recently, there are findings that these membranes may play an effective role in the management of uremic anemia and lead to a reduction in the chronic low-grade inflammatory response of patients with uremic syndrome (Panichi et al, 2011). …”
Section: Vitamin E-coated Polysulfone Membranementioning
confidence: 99%
“…This contributes to the increased cardiovascular morbidity and mortality in that group of patients. Clinical studies point to links between oxidative stress, inflammation, anemia and malnutrition (Panichi et al, 2011). The presence of inflammation and the length of duration of dialysis are the most important determinants of oxidative stress, which make them additional risk factors of cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%